1. The problem statement, all variables and given/known data use laplace transforms to solve the differential equation y"+2y'+17y = 1 2. Relevant equations Initial conditions are y(0) = 0 y'(0) = 0 3. The attempt at a solution so it converts to Y(s) (s^2+2s+17) = 1/s which then ends up as; Y(s) = 1/s*1/(s^2+2s+17) i know i need to invert the equation from laplace again but not sure how. Im not sure if im on the right track by re-arranging to 1/s((s+1)^2+4^2)? Still getting used to spotting laplace eqns. and help would be much appreciated.